2018
DOI: 10.1016/j.celrep.2018.11.035
|View full text |Cite
|
Sign up to set email alerts
|

Polycomb- and Methylation-Independent Roles of EZH2 as a Transcription Activator

Abstract: SUMMARY Enhancer of Zeste 2 (EZH2) is the enzymatic subunit of Polycomb Repressive Complex 2 (PRC2), which catalyzes histone H3 lysine 27 trimethylation (H3K27me3) at target promoters for gene silencing. Here, we report that EZH2 activates androgen receptor (AR) gene transcription through direct occupancy at its promoter. Importantly, this activating role of EZH2 is independent of PRC2 and its methyltransferase activities. Genome-wide assays revealed extensive EZH2 occupancy at promoters marked by either H3K27… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
199
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 221 publications
(212 citation statements)
references
References 22 publications
(39 reference statements)
11
199
1
1
Order By: Relevance
“…ChIP-seq experiments in cell lines revealed substantial co-occupancy of ERG and AR chromatin binding, together with transcriptional corepressors enhancer of zeste homolog 2 (EZH2) and histone deacetylases (HDACs) attenuating AR target gene expression (Kunderfranco et al 2010, Yu et al 2010, Chng et al 2012. However, EZH2 has recently also been reported to activate AR signaling, which is distinct from its conventional role in epigenetic silencing (Kim et al 2018). The non-polycomb repressive complex 2 (PRC2) function of EZH2 is consistent with previous work, which reported enriched AR motifs at EZH2-binding sites depleted of the repressive histone mark H3K27me3 (Xu et al 2012).…”
Section: Erg Fusionssupporting
confidence: 83%
“…ChIP-seq experiments in cell lines revealed substantial co-occupancy of ERG and AR chromatin binding, together with transcriptional corepressors enhancer of zeste homolog 2 (EZH2) and histone deacetylases (HDACs) attenuating AR target gene expression (Kunderfranco et al 2010, Yu et al 2010, Chng et al 2012. However, EZH2 has recently also been reported to activate AR signaling, which is distinct from its conventional role in epigenetic silencing (Kim et al 2018). The non-polycomb repressive complex 2 (PRC2) function of EZH2 is consistent with previous work, which reported enriched AR motifs at EZH2-binding sites depleted of the repressive histone mark H3K27me3 (Xu et al 2012).…”
Section: Erg Fusionssupporting
confidence: 83%
“…These characteristics coincide with other epigenetic regulators such as EZH2. Its emerging methyltransferase‐ and polycomb‐independent roles provide novel therapeutic potential for inhibitors disrupting its docking capacity …”
Section: Discussionsupporting
confidence: 63%
“…Its emerging methyltransferase-and polycomb-independent roles provide novel therapeutic potential for inhibitors disrupting its docking capacity. 39 In line with this model, recent reports in prostate cancer cell lines described a scaffolding role for KDM1A, whereby catalytically inactive KDM1A was still able to establish the prostate cancer gene network and ensure survival of castration-resistant prostate cancer cell lines. 40 This was further confirmed with the tool compound SP2509, proposed as an allosteric inhibitor binding to the H3 pocket region of KDM1A, capable of inducing cell death in prostate cancer cell lines.…”
Section: Global or Promoter-specific Accumulation Of Methylation Of H3k4mentioning
confidence: 73%
“…Earlier data supported the notion that EZH2 overexpression drives emergence of CRPC in a PRC2-independent manner, thus independently of its histone methyltransferase activity (Xu et al 2012). Recently, using a ChIP-seq approach, EZH2 was shown to occupy the AR promoter and act as a transcriptional activator for AR transcription (Kim et al 2018), suggesting that its overexpression in t-NEPCs compared to CRPC adenocarcinomas (Clermont et al 2015) may actually be associated also with its increased coactivator-function rather than its function in deposition of the repressive H3K27me3 mark. Clermont et al showed that several histone-modifying enzymes with chromatin remodeling activity, including CBX2 and EZH2, were upregulated in t-NEPCs as compared to CRPC adenocarcinomas (Clermont et al 2015).…”
Section: Transcription Factor Binding and Chromatin In Neuroendocrinementioning
confidence: 67%